Acceptability of mandatory vaccination: a survey experiment on the effects of thresholds and justifications - Ylisalo Juha; Kulha Katariina; Leino Mikko; Sirén Rasmus; Rapeli Lauri; Setälä Maija (Taylor & Francis, 2025)
Mandatory vaccination might seem like a straightforward solution for reaching a sufficient vaccine coverage during a pandemic. However, the effectiveness of mandatory vaccination is undermined if the public does not perceive such a compulsory policy as acceptable. We report a population-based survey experiment (n = 1,131), conducted in Finland, that addresses the effects that different ways of framing a mandatory vaccination program have on three outcome variables: (1) the perceived acceptability of the program, (2) the willingness to take the vaccine voluntarily, and (3) the preparedness to refuse the mandatory vaccine. In the 2 × 3 factorial experiment, the respondents were presented with one of three justification alternatives that stressed the benefits of the program for either the economy, health, or basic rights. The justification was accompanied with one of two thresholds for herd immunity (70 or 90 percent). We found that the justification and the threshold for herd immunity interact when it comes to the acceptability of the program and the willingness to take the vaccine voluntarily. Importantly, justifications drawing on health were ineffective at the lower threshold level but very effective when the threshold was high. The preparedness to refuse a mandatory vaccine was low and reacted weakly with the experimental treatments.